Green Inovation, Green Intellectual Capital And Good Corporate Governance On Sustainability Performance - Sri Agustina; Yulyanah Yulyanah (-, 2026)
This study examines the influence of innovation, intellectual capital, and governance on sustainability performance. Using purposive sampling techniques and using Stewardship Theory as the theoretical basis, this study focuses on agricultural sector companies listed on the Indonesia Stock Exchange in 2019 and 2023. Data analysis uses panel data analysis with eviews.13 statistical tools. The results of the study show that innovation, intellectual capital, and governance have a positive influence on sustainability performance